Rock shaft resistance of bored piles socketed into decomposed Malaysia granite - Raja Shoib, Raja Shahrom Nizam Shah (2015)
The design of large diameter bored piles socketed into rock has emphasized considerable attention in sedimentary rocks. However, the design only has been occasionally addressed in igneous and metamorphic rocks. Design methods based on the performance of sockets in sedimentary rocks have been proposed in literature, but it is uncertain how applicable they are to other rock types. This paper attempts to review the applicability of the formulae published in the literature in granite formation of Malaysia. A program of field testing tests was conducted to measure the axial response of bored piles. A total of 15 bored piles of diameter varying from 1000mm to 1500mm were constructed in decomposed granite using techniques including advancing of temporary casing and with drilling slurry composed of bentonite fluids. These bored piles were tested with static load test and high strain load dynamic test to verify its integrity and performance and the results of the load tests were evaluated in this study. The results demonstrate that method proposed by Horvath & Kenny gives the best prediction of rock shaft resistance for decomposed granite. The trend of the rock discontinuities were also scattered with relationship to rock shaft resistance and rock compressive strength although proportional increase of rock compressive strength with rock quality designation was observed. Based on the results obtained and the assessment made in this study, it can be deduced that the proposed literature based on sedimentary rocks is applicable to decomposed granite and the maximum rock shaft resistance can mobilise up to 1850kPa in RQD>60%.